Morphometric analysis of the hard palate using cone beam computed tomography in a Saudi population - Yasser A. Araby; Ali S. Alharbi; Shaul Hameed Kolarkodi; Abdulaziz S. Almosyteer (Saudi Dental Journal)
Background and objectives: Analyzing the anatomical and morphometric information of the hard palate is crucial in prosthodontics, orthodontics, maxillofacial surgery, implant dentistry, and forensic anthropology. No data exist in the literature regarding the morphometric analysis of the hard palate using 3D imaging techniques in Saudi Arabia. Therefore, this study aimed to evaluate the dimensions and types of hard palates using 3D geometric morphometrics and the existence of gender-related differences in a selected Saudi population. Material and methods: This cross-sectional study was performed by radiological evaluation of arbitrarily collected Cone Beam computed Tomography (CBCT) images includes 130 male and 45 female individuals from our department’s archives, radiology department, Dental Hospital, Qassim University. The Galileos® Comfort Plus System (Sirona 3D, Germany) was used to obtain the CBCT images while standardizing the parameters. Images were linearly measured using Galileos software. Measurements of palatal length, palatal breadth, and palatal height, as well as the calculation of the palatine index and palatal height index, were noted and statistically analyzed. Results: The mean palatal length, breadth, height, palatine index, and height index were 48.8 ± 3.9 mm, 36.2 ± 3.8 mm, 11.6 ± 2.4 mm, 74.7 ± 8.9, and 32.4 ± 7.1, respectively. The mean palatal length, breadth, and height were greater in men than in women. The majority of the palatine index values corresponded to leptostaphyline (76.6%), followed by mesostaphylline (12%) and brachystaphylline (11.4%), distribution among males and females were not statistical significance (p > 0.05). Palatal height index analysis revealed that the majority were orthostaphyline (59.4%), followed by chamestaphyline (26.3%), and hypsistaphyline (14.3%) these distributions were not significant statistically among males and females(p > 0.05). Conclusion: The palatine index and palatine height index are useful in prosthodontics, orthodontics, and forensic anthropology for identifying races on the basis of the skull.